KEDUDUKAN GRONDKAART SEBAGAI BUKTI PENGUASAAN TANAH (Studi di PT. Kereta Api Indonesia (Persero) Kantor Devisi Regional IV Tanjung Karang) - Karini, Eti (Jurnal Kepastian Hukum dan Keadilan, 2021)
Grondkaart or block maps are documents of evidence of ownership of assets which are assets for an institution or company that must be protected. There are several things that are still debatable regarding the position or legality of Grondkaart itself. One of the state companies that still uses Grondkaart as proof of ownership of its land assets is PT. Kereta Api Indonesia (Persero) or PT. KAI. Land assets of PT. KAI is the legacy of the Dutch railway company which was affected by nationalization, the land often causes disputes due to evidence of land ownership in the form of Grondkaart which is not regulated in Law Number 5 of 1960 and Government Regulation Number 24 of 1997. The rapid development of the current railway must be supported. with the security and management of assets as one of the main capital so that the seizure and control of assets of PT. KAI by unauthorized parties and illegally will not happen again. The problem of this research is how is the position of Grondkaart as proof of land tenure by PT. Kereta Api Indonesia (Persero) Tanjung Karang Regional Division IV Office according to Land Law in Indonesia, and What are the legal consequences of using Grondkaart as proof of land tenure by PT. Kereta Api Indonesia (Persero) Regional Division IV Tanjung Karang Office. This type of research is field research (Field Research) and is carried out descriptively, the problem approach is carried out by empirical juridical, the data used are primary and secondary data, data collection techniques are interviews, observation and documentation, data processing is done by editing, coding , Reconstructing, and Systematizing, then the data were analyzed qualitatively.Keyword:: Grondkaart, Railway, Land Law, Dispute